How to boost your brain power - "Yepsen, Roger, B." (New Delhi, 1992)
Use the strategies in this book to sharpen your thinking skills, focus your powers of concentration, improve your memory and unlock your creativity. The book presents the latest scientific research and current thinking on how mental ability is affected by food, medication, caffeine, alcohol, sleep, light, noise pollution, time of day, stress and ageing and tells your that can do to keep your mental motor running in top gear.
Keywords: Memory